Meningkatkan Pengetahuan Masyarakat Dalam Menggunakan Microsoft Word - Athallah, M. Rifqi Bima; Suharso, Akbar Bayu Kresno; Prakosa, Sagita; Rachmad, Ido Putra Setia; Mustofa, Erlangga Satria; Atsiil, Davin Rozaan; Prasetya, Noven Indra (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2025)
The advancement of the times requires everyone to keep up, including in the ability to use computer programs such as Microsoft Word. Many people in Indonesia still lack proficiency in using Microsoft Word, including residents in the Manukan area, Tandes District, Surabaya City. This community service activity aims to educate the public to understand and be able to operate the basic features of Microsoft Word. The activity was carried out through the delivery of materials and hands-on practice by creating a document. The results showed that participants experienced an improvement in their knowledge and skills in using Microsoft Word. Community service activities like this need to be continuously conducted to enhance technological literacy among people across all age groups.